251 Effects of Cross-Fostering and Number of Litters Used to Create Cross-Fostered Litters on Piglet Pre-Weaning Mortality and Weaning Weight. (12th April 2022) - Vande Pol, Katherine D; Olivio, Alicia; Harper, Heath; Shull, Caleb M; Brown, Katie; Ellis, Michael
Abstract: The objective was to determine effects of cross-fostering and number of litters used to create cross-fostered litters on piglet pre-weaning mortality (PWM) and weight. The study was conducted on 2 commercial farrowing facilities using a RCBD (53 blocks; total of 265 litters/3675 piglets). Blocking factors were farrowing day, sow parity, body condition score, functional teat number, and average and CV of piglet birth weight. Treatments involved cross-fostering different percentages of the litter (0% = no cross-fostering; 50% = half cross-fostered, half from the birth sow; 100% = all piglets cross-fostered) and differing number of litters used in cross-fostering. The 5 Treatments were (% fostered/number of litters used): 1) 0%/1 litter; 2) 100%/1 litter; 3) 100%/6+ litters; 4) 50%/4+ litters; 5) 50%/2 litters. Litter sizes at cross-fostering (13 or 14 piglets) were equalized across Treatments within block. Piglets were weighed 24 h after birth (when cross-fostering was carried out) and at weaning (19.2 ± 0.97 d); all PWM was recorded. Data were analyzed using SAS, models accounted for the fixed effect of Treatment and random effects of sow, block, and farm. The 0%/1 litter and 100%/1 litter Treatments were similar ( P > 0.05; Table 1) for all measurements, indicating no effect of cross-fostering per se. Litter sizes at 7 and 14 d, and weaning were lower ( P ≤ 0.05) for the two 1-litter Treatments compared with the 50%/2 litters Treatment; other Treatments were intermediate. There was no effect ( P > 0.05) of Treatment on piglet weight. Pre-weaning mortality was greater ( P ≤ 0.05) for the two 1-litter treatments compared with the other 3 Treatments, which were similar ( P > 0.05). In conclusion, cross-fostering had no effect on piglet performance, however, PWM was greater for treatments comprised of piglets from a single litter compared with those from several litters.